1997
DOI: 10.1002/(sici)1099-1395(199708)10:8<600::aid-poc928>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Solvolysis-decomposition ofN-1-adamantyl-N-p-tolylcarbamoyl chloride in hydroxylic solvents

Abstract: In hydroxylic solvents, N-1-adamantyl-N-p-tolylcarbamoyl chloride undergoes a facile rate-determing ionization with very little assistance from nucleophilic solvation (very low sensitivity to changes in solvent nucleophilicity). In the relatively nucleophilic aqueous ethanol or aqueous acetone, the cation formed reacts directly with the solvent. In fluoroalcohols, the low nucleophilicity of the solvent allows an effective competition from a pathway involving disproportionation to the 1-adamantyl cation and p-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The elimination of dispersion effect when p ‐methoxybenzyl chloride is taken as a standard for comparison showed that the 1,2‐diphenylethyl system behaves similar to the 1‐phenylethyl system. The dispersion effect thus can be eliminated without the use of the extended Winstein equation (Eqn (3)) with aromatic ring factor ( I ), which has been proposed to eliminate the dispersion due to the aromatic ring contributions26, 70–71 and also the steric and electronic factors 37, 38. In the present system, electronic and steric factors are important in stabilizing the carbocation; the comparison with a suitable standard substrate ( p ‐methoxybenzyl chloride) eliminates the dispersion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The elimination of dispersion effect when p ‐methoxybenzyl chloride is taken as a standard for comparison showed that the 1,2‐diphenylethyl system behaves similar to the 1‐phenylethyl system. The dispersion effect thus can be eliminated without the use of the extended Winstein equation (Eqn (3)) with aromatic ring factor ( I ), which has been proposed to eliminate the dispersion due to the aromatic ring contributions26, 70–71 and also the steric and electronic factors 37, 38. In the present system, electronic and steric factors are important in stabilizing the carbocation; the comparison with a suitable standard substrate ( p ‐methoxybenzyl chloride) eliminates the dispersion.…”
Section: Resultsmentioning
confidence: 99%
“…The above equation was also applied to systems having aromatic ring that cannot enter into conjugation with the developing carbocationic centre37 and even to systems which have no aromatic ring at all and the dispersion observed is due to steric crowding at the carbocationic centre 38. The introduction of an adjustable parameter in linear equation thus has no relevance to aromatic ring contribution but simply brings the value of correlation coefficient to unity and the standard deviation to zero.…”
Section: Introductionmentioning
confidence: 99%
“…A study was carried out [62] to see whether a parallel pathway would be observed with a 1-adamantyl group on the nitrogen of a carbamoyl chloride. Since the other group was an aryl group, this study will be discussed in the next section of this review.…”
Section: Solvolyses Of Nn-dialkylcarbamoyl Chloridesmentioning
confidence: 99%
“…The solvolyses of N -1-adamantyl- N - p -tolylcarbamoyl chloride have been studied in terms of kinetics and products in alcohols, aqueous alcohols, aqueous acetone and 2,2,2-trifluoroethanol (TFE)-ethanol mixtures [62]. For ethanolyses at 50.0 °C, the rates are intermediate between those for the diethyl and diisopropyl derivatives and it was suggested that an accelerative effect from introduction of a tert -alkyl group was counterbalanced by a retarding effect on introducing the aryl group.…”
Section: Solvolyses Of N-alkyl-n-arylcarbamoyl Chloridesmentioning
confidence: 99%